The Reality of The Iraqi Economy and Foreign Direct Investment - Kerah Kazar, Fadhel (Indonesian Journal of Humanities and Social Sciences, 2023)
One of the most important sources of financing in foreign investments isthat it has a significant role as one of the components of economic growthand works to increase productivity in the economy, improve theemployment rate, and provide new job opportunities and advancedscientific knowledge. In Iraq, public and private direct investmentswitnessed a significant decline due to economic, political and securityfactors, which negatively affected economic life. The research includedthe introduction, the research problem and its importance, and the firsttopic, which dealt with the concept of investment and its types. Thesecond topic dealt with the reality of the Iraqi economy, while the thirdtopic explained the extent of the Iraqi economy’s need for foreign directinvestment.